Expression profile and overexpression outcome indicate a role for βKlotho in skeletal muscle fibro/adipogenesis. (13th April 2016) - Phelps, Michael; Stuelsatz, Pascal; Yablonka‐Reuveni, Zipora
Abstract : Regeneration of skeletal muscles is required throughout life to ensure optimal performance. Therefore, a better understanding of the resident cells involved in muscle repair is essential. Muscle repair relies on satellite cells (SCs), the resident myogenic progenitors, but also involves the contribution of interstitial cells including fibro/adipocyte progenitors (FAPs). To elucidate the role of the fibroblast growth factor (FGF) signaling in these two cell populations, we previously analyzed freshly isolated cells for their FGF receptor (FGFR) signature. Transcript analysis of the four Fgfr genes revealed distinct expression profiles for SCs and FAPs, raising the possibility that these two cell types have different FGF‐mediated processes. Here, we pursued this hypothesis exploring the role of the Klotho genes, whose products are known to function as FGFR co‐receptors for the endocrine FGF subfamily. Isolated SC and FAP populations were analyzed in culture, exhibiting spontaneous myogenic or adipogenic differentiation, respectively. αKlotho expression was not detected in either population. βKlotho expression, while not detected in SCs, was strongly upregulated in FAPs entering adipogenic differentiation, coinciding with expression of a panel of adipogenic genes and preceding the appearance of intracellular lipid droplets. Overexpression of βKlotho in mouse cell line models enhanced adipogenesis in NIH3T3 fibroblasts but had no effect on C2C12 myogenic cells. Our study supports a pro‐adipogenic role for βKlotho in skeletal muscle fibro/adipogenesis and calls for further research on involvement of the FGF–FGFR–βKlotho axis in the fibro/adipogenic infiltration associated with functional deterioration of skeletal muscle in aging and muscular dystrophy. Abstract : We report novel findings on βKlotho role in skeletal muscle fibro/adipogenesis. Endogenous βKlotho, while absent in satellite cells, was upregulated in fibro/adipocyte progenitors coinciding with their adipogenic differentiation. Additionally, βKlotho overexpression promoted adipogenic differentiation in fibroblastic but not in myogenic cells. This study establishes a new research direction for combating muscle fibrosis and adiposity associated with aging and muscular dystrophy.